2016
DOI: 10.5937/matmor1602143z
|View full text |Cite
|
Sign up to set email alerts
|

Existence and exponential stability of solutions for transmission system with varying delay in R

Abstract: In the present paper we are going to consider in a one dimension bounded domain a transmission system with a varying delay. Under suitable assumptions on the weights of the damping and the delay terms, we prove the well-possedness and the uniqueness of solution using the semigroup theory. Also we show the exponential stability by introducing an appropriate Lyaponov functional.2000 Mathematics Subject Classification. Primary: 435B37; Secondary: 35L55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(24 reference statements)
4
8
0
Order By: Relevance
“…In the present work we improve the results in [27] where, for constant weights µ 1 (t) = µ 1 , µ 2 (t) = µ 2 and under adequate assumptions regarding the weight and time-varying delay, was proved the well posedness and singularity of solutions by using the semigroup theory. Authors also showed exponential stability by introducing an appropriate Lyapunov functional.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present work we improve the results in [27] where, for constant weights µ 1 (t) = µ 1 , µ 2 (t) = µ 2 and under adequate assumptions regarding the weight and time-varying delay, was proved the well posedness and singularity of solutions by using the semigroup theory. Authors also showed exponential stability by introducing an appropriate Lyapunov functional.…”
Section: Introductionsupporting
confidence: 57%
“…Under an appropriate assumption on the weights of the two feedbacks (µ 1 < µ 2 ), it was proved the well-posedness of the system and, under condition (1.7), it was established an exponential decay result. The result in [6] were improved by S. Zitouni et al [27]. There, the authors considered the problem with a time-varying delay τ (t) of the form (1.9)…”
Section: Introductionmentioning
confidence: 99%
“…which is the same as that in Marzocchi et al [21] and similar to Datko [10] and Zitouni et al [16]. This assumption can be viewed as a restriction on the wave speeds of the two different materials.…”
Section: Introductionmentioning
confidence: 52%
“…. This is different from previous studies [16][17][18][19][20][21]29] and has not been studied by previous studies [27,28,30]. (iii) Under the assumption of 𝜉, Kato's variable norm technique can be used to obtain the well-posedness from Cauchy problem (2.7) with a non-autonomous operator  in (2.8).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation